Kampung Sutera community assistance in making educational photo spots from glass waste - M. Imron Mas'ud; Muhammad Dicky Dwi Cahya; Dwi Rizqi Alfajar; Khoiriyah Khoiriyah; Muhammad Nasichun Amin; Dhurotun Nafi'ah; Nur Iva Apriliyah; M. Ubaidillah; Nicco Ryantino; M. Ainun Najib; Dafina Agustina; Nazilatul Maghfiroh; Hela Wardani; Lailatul Khasana (Universitas Muhammadiyah Magelang, 2021)
The need for a variety of photo spots in educational tours is very important. It aims to increase public interest in learning, so that the number of visitors will increase. This community service program aims to empower the community through assistance in making photo spots on educational tours of Kampung Sutera in Sentul Village, Purwodadi District, Pasuruan Regency. The method is carried out through photo spot design, selection and separation of glass, as well as the execution process in manufacturing. A new photo spot location that visitors can use with a butterfly nuance is the result from this service.